Factors that impact the financial performance of broiler production in southern states of Paraná, Brazil - Mendes,AS (2014)
This study aimed at identifying the factors that affect the financial performance of broiler chicken production in Southwest of Paraná state in Brazil, as well as to study the relationship of these factors with the social-economic situation of poultry farmers. Data were obtained from a questionnaire applied to broiler chicken farmers between February and March, 2011. The questionnaire included 39 questions relative to farmer's age, family size, land possession, capital invested in broiler farming, gross income per flock, training and broiler farming experience, production size, credit needs, technical service, labor, production problems, and bird weight at slaughter. Data were submitted to descriptive statistical analysis. The relationship between production data and financial performance was determined using Pearson correlation coefficient, at 95% confidence level. Approximately 64.84% of the interviewed broiler farmers in Paraná state presented medium to low financial performance. Factors such as education level, facility size, labor, gross income per flock, and average bird weight at slaughter had a positive impact on financial performance. The production problems that most affected the broiler production were environmental challenges, poor feed conversion, as well as management problems and low-quality chicks.